ESTRATÉGIAS DE LONGO PRAZO PARA PROMOÇÃO DO EQUILÍBRIO FINANCEIRO E ATUARIAL DE REGIMES PRÓPRIOS DE PREVIDÊNCIA SOCIAL - MURARO, ANDREI MARCEL (2022)
Social security is meant to assist citizens in times when they need it the most, which may be illness or even advanced age, after a long working life. In the public service context, states and municipalities have been allowed to create their own Special Social Security System, taking responsibility for this scheme, which impacts not only the public servants, but also the local society due to the consumption of public resources that must eventually be directed to the maintenance of these entities. The social security statistical yearbooks show that there is an important imbalance involving the Special Social Security System, which can be aggravated by factors such as demographic changes. Thus, actions aimed at the search for balance in these entities are necessary, given the socioeconomic impact and the use of public resources. In view of this, the present work proposed to investigate which strategic actions have been developed by Special Social Security System in the State of Paraná with a view to actuarial balance. The study used a qualitative approach, developing a multiple case study involving five organizations located in different municipalities of the state of Paraná. Interviews were conducted with those responsible for the entities and content analysis of the data collected. The analytical categories are structured under the foundation of public finance theory, exploring the variables public revenue, public expenditure, system balance and government failure. As a result, it was found that the main actions developed by these regimes are: reform of benefits; use of contributions; increase of aliquots; specific supplementary aliquot for professionals with less time of contribution; alteration in the equating method, with purchase of lives and offers of guarantee from the entity to the Special Social Security System; search for new sources of collection, such as photovoltaic plants, buildings for rent, concession of administration of bus stations, partnerships with institutions that explore the activity of recyclables; active management of investments; offer of consigned loans as a form of investment and adhesion to the pro-management to promote improvement of the organizational structure.